Synthesis and Antimicrobial Studies of New [Tetrakis (1, 2, 4-Triazole / 1, 3, 4-Oxadiazole / 1, 3, 4-Thiadiazole] [Bis-(Benzene-1, 3, 5-Triyl)] Dioxymethylene Compounds - Ayyash, Ahmed Neamah (Iraqi Journal of Science, 2020)
Synthesis of new heterocyclic compounds containing four five-membered rings together was the main goal of this work. The new derivatives of [tetrakis (1,2,4-triazole /1,3,4-thiadiazole /1,3,4-oxadiazole][bis-(benzene-1,3,5-triyl)] dioxymethylene A7-A18 were synthesized by the reaction of [bis-(dimethyl 5-yl-isophthalate)] dioxymethylene compound A1 which was previously prepared from the reaction of 1,2-dibromomethan and dimethyl 5-hydroxyisophthalate, then treated with hydrazine hydrate to yield the corresponding acid hydrazide A2. In the next step, compound A2 was refluxed with 4-substituted isothiocyanate to give substituted thiosemicarbazides A3-A6. The treatment of the latter compounds in basic medium of 2M of NaOH afforded 1,2,4-Triazole derivatives A7-A10. Whereas the reaction of the same compounds with concentrated sulfuric acid gave 1,3,4-thiadiazoles A11-A14. Furthermore, the new derivatives of 1,3,4-oxadiazole A15-A18 were obtained by the reaction of thiosemicarbazides and tosyl chloride in presence of pyridine. (C. H. N.) elemental analysis, FT-IR, and 1HNMR techniques were used to characterize the chemical structure of some of the new synthesized compounds which also exhibited an important biological activity.